A Case Study of the Sasak People in Sade Village, NTB: Mopping Tradition with Cow Dung and the Risk of ARI - Lalu Amri Yasir; Anna Layla Salfarina; Jora Firdha Kholaeda; Dewi Fitriana; Baiq Nurul Hidayati (Institut Kesehatan YARSI Mataram, 2025)
In West Nusa Tenggara Province, acute respiratory infections pose a serious health risk, particularly to young children. Understanding the custom of utilizing cow dung in Sade Village, Central Lombok Regency, and determining its association with ARI risk are the objectives of this study. The the method of case studies, qualitative research is employed to fully comprehend the custom of mopping with cow dung to reduce the danger of ISPA. According to the findings, there was a substantial negative influence on health, particularly for children between the ages of one and six, when cow dung was used as a cleaning agent and floor glue. Due to the possibility of airborne and dustborne contamination, the risk of ARI rises when cow dung contains pathogenic bacteria. This conclusion is reinforced by data on pediatric illnesses in Sade Village, such as colds, coughs, allergies, and diarrhea, which are correlated with frequent ARI symptoms. The link between cultural and health factors in the Sade Village community is complicated, and this research helps to clarify that. A comprehensive education effort is required to offer a clearer awareness of the connection between the dangers of ARI and cow dung usage practices. ABSTRAK Di Provinsi Nusa Tenggara Barat, infeksi saluran pernapasan akut menimbulkan risiko kesehatan yang serius, terutama pada anak-anak. Mengetahui kebiasaan memanfaatkan kotoran sapi di Desa Sade, Kabupaten Lombok Tengah, dan mengetahui hubungannya dengan risiko ISPA menjadi tujuan penelitian ini. Metode studi kasus, penelitian kualitatif digunakan untuk memahami sepenuhnya kebiasaan mengepel dengan kotoran sapi untuk mengurangi bahaya ISPA. Berdasarkan hasil penelitian, terdapat pengaruh negatif yang cukup besar terhadap kesehatan, terutama pada anak-anak berusia antara satu sampai enam tahun, ketika kotoran sapi digunakan sebagai bahan pembersih dan perekat lantai. Karena kemungkinan kontaminasi melalui udara dan debu, risiko ISPA meningkat ketika kotoran sapi mengandung bakteri patogen. Kesimpulan ini diperkuat dengan data penyakit anak-anak di Desa Sade, seperti pilek, batuk, alergi, dan diare, yang berkorelasi dengan gejala ISPA yang sering terjadi. Keterkaitan antara faktor budaya dan kesehatan di masyarakat Desa Sade rumit, dan penelitian ini membantu memperjelas hal tersebut. Diperlukan upaya edukasi yang komprehensif untuk memberikan kesadaran yang lebih jelas tentang hubungan antara bahaya ISPA dan praktik penggunaan kotoran sapi.